Engineering Electromagnetics - Ida, Nathan, author 251214 (Cham, Switzerland : Springer Nature Switzerland AG, 2021)
This comprehensive two semester textbook, now in its 4th edition, continues to provide students with a thorough theoretical understanding of electromagnetic field relations while also providing numerous practical applications. The topics follow a tested pattern familiar to the previous edition, each with a brief, introductory chapter folled by a chapter with extensive treatment, 10 to 30 applications, examples and exercises, and problem and summaries. There is new emphasis on problems, examplesand applications based on energy harvesting and renewable energy; additional information on sensing and actuation, new material on issues in energy, power, electronics, and measurements, and an emphasis on aspects of electromagnetics relevant to digital electronics and wireless communication. The author adds and revises problems to emphasize the use of tools such as Matlab; new advanced problems for higher level students; a discussion of symbolic and numerical integration; additional examples with each chapter; and new online material including experiments and review questions. The book is an undergraduate textbook at the upper division level, intended for required classes in electromagnetic. It is written in simple terms with all details derivations included and all step in solutions listed. It requires little beyond basic calculus and can be used for self-study. Features hundreds of examples and exercises, many new or revised for every topic in the book; Includes over 650 end-of-chapter problems, many of them new or revised, mostly based on applications or simplified applications; Includes a suite of online demonstartion software including a computerized Smith Chart.